2018
DOI: 10.4066/biomedicalresearch.29-18-337
|View full text |Cite
|
Sign up to set email alerts
|

Serum ischemia modified albumin (IMA) levels of patients with bipolar disorder in remission and healthy controls

Abstract: Oxidative stress might play an important role in neurological and psychiatric diseases due to the central nervous system sensitivity to reactive oxygen species. Aim of this study is to contribute these data about oxidative stress in bipolar disorder, by detecting IMA levels of bipolar disorder patients in remission and also by comparing these results with healthy controls. Study population consisted of 35 outpatients with bipolar disorder, who being in remission. The patients meeting the Diagnostic and Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Increased IMA levels have also been found in patients with major depressive disorder. One study reported a positive correlation between the severity of depression and IMA levels [100], but another study did not detect a significant difference between IMA levels in the serum of patients with bipolar disorder during remission and healthy controls [102]. In contrast, Tunç et al detected increased IMA levels in bipolar disorder patients during remission, although they found no IMA changes in unipolar depression patients [101].…”
Section: Neurological Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased IMA levels have also been found in patients with major depressive disorder. One study reported a positive correlation between the severity of depression and IMA levels [100], but another study did not detect a significant difference between IMA levels in the serum of patients with bipolar disorder during remission and healthy controls [102]. In contrast, Tunç et al detected increased IMA levels in bipolar disorder patients during remission, although they found no IMA changes in unipolar depression patients [101].…”
Section: Neurological Disordersmentioning
confidence: 97%
“…IMA's diagnostic value in psychiatric disorders, such as AD, schizophrenia, and bipolar disorders, is controversial [101,102]. An increase in IMA, IMAR, and some markers for oxidative stress, such as advanced oxidation protein products (AOPP), ceruloplasmin, and prooxidant-antioxidant balance (PAB), has been shown in AD, the most common form of dementia in the elderly population [99,119].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…In a study, no significant difference was found in serum IMA levels in bipolar disorder patients during the remission period when compared with the control group [22]. However, another study showed increased IMA levels in bipolar disorder patients during the remission period as compared to the control group, but no significant difference was found in unipolar depression patients [23].…”
Section: Discussionmentioning
confidence: 91%